STUDI KOMPARATIF PADA KINERJA KEUANGAN BANK PERKREDITAN RAKYAT (BPR) PADA MASA SEBELUM DAN SAAT PANDEMI COVID-19 - Muhammad Rosidi; Zaky Zakiyya (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2022)
BPR Bank are one of the heroes in lending, especially to small people and also micro, small and medium enterprises or MSMEs. During this pandemic, the performance of BPR is one that needs to be highlighted and important. So in this study a comparison was made on activities before the pandemic and at the time of the Covid-19 pandemic for the financial or health performance of BPR. Meanwhile, in this study, qualitative and quantitative analysis was carried out. Several secondary documents were given which were analyzed in terms of LBR, BOPO and others. In this case, what is in the spotlight is the ability to pay credit which is indeed affected by the Covid-19 pandemic. In an effort to survive during this pandemic, BPR is expected to be able to transform from conventional to digitalization.